Swath sonar multibeam EM122 bathymetry raw data during transits of SONNE cruises SO268/1 and SO268/2, Pacific - Iason-Zois Gazis; Peter Urban; Matthias Haeckel; Anne-Cathrin Wölfl (PANGAEA, 2020)
Data acquisition was performed using the multibeam echosounder Kongsberg EM122. Raw data are delivered in Kongsberg. all format. The data acquisition was part of the international project JPI Oceans - MiningImpact Environmental Impacts and Risks of Deep-Sea Mining.